Detection of Aberrant Phenotypes in Acute Leukemia Patients in Relation to Some Hematological Parameters - Hisham Ahmed Moustafa; Karima Abdel-Halim Mahfouz; Mamdouh Mohamed; Mahmoud Mohamed Bazeed (International Journal of Medical Arts, 2023)
Background: Patients with acute leukemia [AL] may express aberrant antigens that are normally restricted to a different lineage. We evaluated the frequency of aberrancy in AL patients.Aim of the work: Evaluation and analysis of the incidence of aberrant phenotypes in mononuclear cells in AL patients and their relation to hematological parameters.Patients and Methods: This observational descriptive study was conducted on 150 newly diagnosed cases of AL over the period from August 2017 to March 2021. Flow cytometry was performed by Becton Dickinson [BD] FACS Calibur/BD FACS Canto flow cytometers using monoclonal antibodies against cell markers.Results: The overall frequency of aberrancy was 38.7% [58/150] in all AL patients. Aberrant antigenic expression was more frequent in acute lymphoblastic leukemia [ALL] than acute myeloid leukemia [AML], T-ALL with aberrant expression was 66.6% of all T-ALL patients, while B-ALL with aberrant expression was 45.8% of all B-ALL patients, and AML with aberrant expression was 31.1% of all AML patients.Conclusion: Aberrant phenotypes were found with considerable frequency in AL patients, and the implication of aberrant markers can help in disease monitoring, detecting measurable residual disease, and determining risk stratification and treatment intensity.